Isothermal structural evolution of SnO2 monolithic porous xerogels - Brito, GES; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Craievich, A. F. (Munksgaard Int Publ Ltd, 1997)
Monolithic samples of SnO2 xerogel were produced by careful control of the gelation and drying steps of material preparation. In these samples, small and nanoporous aggregates stick together, yielding a monolithic (nonpowdered) material. The material was analyzed by in situ small-angle X-ray scattering (SAXS) during isothermal treatment at temperatures ranging from 473 to 773 K. At 473 K, the SAXS intensity does not change significantly with time. All experimental scattering intensity functions for T > 473 K are composed of two wide peaks, which evolve with increasing time. Each of them was associated with one of the modes of a bimodal distribution of pore sizes corresponding to a fine (intra-aggregate) and a coarse (inter-aggregate) porosity. The SAXS intensities of the maxima of both peaks increase with increasing treatment time, while the position of their maxima, associated with an average correlation distance, decreases. The time dependences of the SAXS intensity corresponding to both families of pores qualitatively agree with those expected for a two-phase separating system exhibiting dynamic scaling properties. The time evolutions of the several moments of the structure function of samples heat treated at 773 K exhibit a good quantitative agreement with the theory of dynamic scaling for systems evolving by a coagulation mechanism. The kinetic parameters are the same for both peaks, indicating that the same mechanism is responsible for the structural evolution of both families of pores.